Photo Stabilization of Poly (Vinyl Chloride) Films by Some Nickel Complexes - Ahmed Salim Ibrahim (Academic Science Journal)
This study looked at the utilization of certain nickel complexes and their effects on the photodegradation of poly vinyl chloride. PVC films were cast using a 0.05 w/w by weight compound concentration Tetrahydrofuran (THF) solvent (80µm thickness). Numerous techniques, including measuring the carbonyl (ICO)index, calculating the photodegradation rate constant (kd) and tracking changes in the average molecular weight of PVC films with and without additives while increasing irradiation time, were used to determine the photodegradation and photo stabilization activities of these compounds. The order of these additives' photo stabilization activity is as follows: